REGULASI PENDIDIKAN NASIONAL SEBAGAI UPAYA MENINGKATKAN SUMBER DAYA MANUSIA MEMASUKI ERA MASYARAKAT EKONOMI ASEAN (MEA) - Yuli W, Yuliana; Yayitarina, Dwi Desi (Jurnal Yuridis, 2016)
Entering the era of MEA, HR Indonesia absolutely must be improved in order to be on par with SDM countries in the ASEAN region. Socio-cultural aspects necessary for the development of human resources (HR) through education. With hope, when the ASEAN community-level human resources is equivalent (equal), will furtheraccelerate economic integration as the main pillars of the ASEAN Community.Therefore, it is important the holding of the ASEAN countries to increase cooperation in the field of education. This cooperation is to improve the quality of human resources, especially pupils and students in the ASEAN region. This study discusses the regulatory history of education in Indonesia and the implementation of the regulations of national education to develop human resources capable of competing in the MEA.